General and Maladaptive Traits in a Five-Factor Framework for DSM-5 in a University Student Sample. (June 2013) - De Fruyt, Filip; De Clercq, Barbara; De Bolle, Marleen; Wille, Bart; Markon, Kristian; Krueger, Robert F.
The relationships between two measures proposed to describe personality pathology, that is the Revised NEO Personality Inventory (NEO-PI-3) and the Personality Inventory for DSM-5 (PID-5), are examined in an undergraduate sample ( N = 240). The NEO inventories are general trait measures, also considered relevant to assess disordered personality, whereas the PID-5 measure is specifically designed to assess pathological personality traits, as conceptualized in the DSM-5 proposal. A structural analysis of the 25 PID-5 traits confirmed the factor structure observed in the U.S. derivation sample, with higher order factors of Negative Affectivity, Detachment, Antagonism, Disinhibition, and Psychoticism. A joint factor analysis of, respectively, the NEO domains and their facets with the PID-5 traits showed that general and maladaptive traits are subsumed under an umbrella of five to six major dimensions that can be interpreted from the perspective of the five-factor model or the Personality Psychopathology Five. Implications for the assessment of personality pathology and the construction of models of psychopathology grounded in personality are discussed.